Oropharyngeal colonization with Legionella pneumophila. - Bridge, J A (1983)
A total of 186 volunteers, including 40 hospital patients, participated in a cross-sectional survey of oropharyngeal colonization with Legionella pneumophila. Colonization was defined as the appearance of any L. pneumophila organisms on culture or a positive direct fluorescent-antibody (FA) test or both in the absence of signs or symptoms of pneumonia. The direct FA tests were performed on throat swabs, using a polyvalent conjugate directed against L. pneumophila serogroups I through IV. Throat swabs were cultured for L. pneumophila on a selective medium. Blood specimens were tested for antibody, using an indirect FA test and heat-killed polyvalent antigen for L. pneumophila serogroups I through IV. Eight people, none of whom had pneumonia or fever, had positive direct FA tests; no subject had a positive culture for L. pneumophila. Whether the positive direct FA results represent colonization cannot be stated with assurance. In any case, the results suggest that colonization occurs infrequently.